Effects of Obesity on Vascular Potassium Channels - Climent, Belen; Simonsen, Ulf; Rivera, Luis (Current Vascular Pharmacology, 2014)
This review is focused on the effects of obesity on function and expression of potassium (K) channels in the vasculature. Five families of K channels have been identified in the vascular wall, calcium-activated K (KCa) channels, inward-rectifier K (KIR) channels, ATP-sensitive K (KATP) channels, voltage-gated K (KV) channels and two-pore domain K (K2P) channels. In endothelial cells (EC) and vascular smooth muscle cells (VSMC) opening of K channels leads to hyperpolarisation followed by vasodilatation. In some vascular beds of animal models of obesity, vasodilatation mediated by KCa3.1 and KCa2.3 channels has been reported to remain unaltered or even increased, whereas vasodilatation involving KCa1.1 channel has consistently been reported to be impaired. Changes in expression and function of KIR and KATP channels have also been associated with impaired vasodilatation in animal models of obesity, and therefore activation of these channels may improve endothelial function and reduce the risk of major cardiovascular events. Expression of KV7.x channels is downregulated in small arteries from hypertensive animals and it would be interesting to assess whether these channels contribute to development of hypertension in obese patients. However, the role of KV7.x and K2P channels in regulation of blood pressure remains unexplored compared to other K channels. In conclusion, obesity and metabolic syndrome alter expression, function and sensitivity of vascular K channel subtypes causing smooth muscle dysfunction and probably endothelial dysfunction which makes these patients particularly prone to premature cardiovascular disease. Modulation of K channel activity by use of openers of e.g. KCa and KATP channels may also be attractive to counteract vascular dysfunction observed in obesity.
Keywords: KCa channels